No place like home: A study of two homeless shelters - Friedman, Bruce David (Journal of Social Distress and The Homeless, 1994)
Homelessness is one of the most pressing social problems today. Society has responded to the problem with the creation of homeless shelters. Yet, the nature of the operation of the shelter is not defined. This study explored the operations of two single adult homeless shelters to understand how they operate in addressing the problem of homelessness. The study identified two different types of services, one called `'house” and the other `'home”. House services provided basic food, shelter, and linkage to social services, which fulfilled the basic definition of the problem of homelessness as defined by the Institute of Medicine. Home services provided the basic services of house but also went one step beyond by providing these services within the context of a supportive environment, thus creating informal social supports. The study discusses the implications of each of these modalities in addressing the problems associated with people who are homeless as well as the differences in policies and structures which contribute to one shelter providing house and the other home services.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/063-532-898-166-966 tex.type: [object Object]
Keywords: dept.swk